Attribute analysis as a tool for determining the areas of the late diagenetic Main Dolomite deposits and assessing the stability of the seismic signal parameters - Smalera, Norbert (Geology, Geophysics and Environment, 2022)
The results of the lithofacial analysis of data from the Moracz 3D seismic survey were among the main premises leading to the positioning of the new petroleum exploration well in that area. Unfortunately, the reservoir properties of the drilled part of the Main Dolomite carbonates differed significantly from those anticipated by the analysis of the amplitudes of the seismic signal recorded. Such surprisingly negative results impelled the reinterpretation of 3D seismic data. Hence, a number of analyses of the amplitudes, the frequencies, and the variability of phase shift were carried out in order to determine the influence of these parameters on the lithofacial interpretation of seismic data. The results revealed a fundamental error of amplitude with the extraction maps. It appeared that the distribution of amplitudes is not essentially controlled by the reservoir properties of the Main Dolomite carbonates but by the fault shadow effect coming from Mesozoic graben in the overburden. In addition, a large diversity of frequency spectra was found, which, combined with the small thickness of the exploration level, could have contributed to incorrect identification of seismic reflections. There was also a change in seismic signatures from the same reflection in different parts of the survey, raising doubts about the distribution of the phase rotation. In order to recognize phase rotation diversity, a new seismic data analysis was based upon the selected Triassic sediments of high impedance. The obtained maps demonstrated significant variability within the data volume due to attenuation. The reinterpreted data from the Moracz 3D seismic survey proved the uneven and unstable distribution of amplitudes, frequencies, and phase which resulted in erroneous conclusions of petroleum exploration. After modeling with the use of different frequency ranges, an analysis of the amplitude extraction of the horizons related to the Main Dolomite was performed. Then the amplitude ratio attribute was selected which eliminated the influence of the regional amplitude and frequency distribution and showed the distribution of dolomite properties more reliably than the amplitude extraction maps.